Rye and Health 2014
DOI: 10.1016/b978-1-891127-81-6.50011-0
|View full text |Cite
|
Sign up to set email alerts
|

Satiating Effects of Rye Foods

Abstract: The satiating capacity of foods and meals is affected by caloric content, but also varies with several aspects of food composition (e.g. macronutrient composition, energy density, fibre content and food structure). Rye is a cereal that possesses interesting characteristics with the potential to increase satiety. There are currently public health threats related to overweight and obesity, conditions that result from energy intake exceeding energy output. Excessive energy intake can be avoided by diets based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 133 publications
(172 reference statements)
0
2
0
Order By: Relevance
“…The larger 55-g rye porridges with or without inulin and wheat gluten increased satiety more than the small 40-g rye porridge, and the effect was strongest during the period before lunch (0-240 min). The importance of portion size was demonstrated by Isaksson (48) : inclusion of 55-66-g rye per portion porridge lowered appetite, whereas 45-g rye per portion bread did not, in comparison with WB. In contrast, Forsberg et al (5) showed less pronounced effects on appetite following intake of 80 g instead of 64-g rye crisp bread compared with WB.…”
Section: Discussionmentioning
confidence: 99%
“…The larger 55-g rye porridges with or without inulin and wheat gluten increased satiety more than the small 40-g rye porridge, and the effect was strongest during the period before lunch (0-240 min). The importance of portion size was demonstrated by Isaksson (48) : inclusion of 55-66-g rye per portion porridge lowered appetite, whereas 45-g rye per portion bread did not, in comparison with WB. In contrast, Forsberg et al (5) showed less pronounced effects on appetite following intake of 80 g instead of 64-g rye crisp bread compared with WB.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent meta-analysis including 23 studies concluded that a 15% change in self-reported satiety on a VAS-scale was associated with significant change in food intake [ 13 ]. In total, about 25 short-term studies have been published on the short-term post-meal satiety after intake of 60 different fiber-rich cereal food products [ 14 ]. Many of the studies reported increased satiety, suppressed hunger and/or a decreased in energy intake in a subsequent meal after consumption of foods rich in fiber or whole grain compared with iso-caloric portions of low-fiber control foods [ 14 ].…”
Section: Introductionmentioning
confidence: 99%